Motion-Accurate Allocation of a Mechanical Transmission System Based on Meta-Action and Intuitionistic Trapezoidal Fuzzy Numbers - Zongyi Mu; Jian Li; Xiaogang Zhang; Genbao Zhang; Jinyuan Li; Hao Wei (Actuators)
The traditional mechanical transmission system motion accuracy allocation process has the following problems: the error modeling process can not reflect the error formation mechanism of the system, and the influence of maintenance costs and the motion accuracy robustness of the system are ignored in the process of establishing the optimal allocation model of motion accuracy. In this paper, firstly, meta-action theory is introduced and the meta-action unit is taken as the basic analysis unit, the error modeling of mechanical transmission systems is studied, and the formation mechanism of the motion error is correctly analyzed. Secondly, the comprehensive cost of a mechanical transmission system, considering the part manufacturing cost, assembly cost and maintenance cost per unit, is accurately evaluated using the multi-criteria decision-making (MCDM) method. Thirdly, based on the motion error model, a robust model for system motion accuracy is obtained by analyzing the sensitivity of each motion pair. Then, a multi-objective optimal allocation model of motion accuracy is established. The model is solved by an intelligent algorithm to obtain the Pareto non-dominated solution set, and the optimal solution is selected by the fuzzy set method. Finally, the method described in this paper is illustrated by an engineering example.